2022
DOI: 10.1002/npr2.12304
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neuropeptide levels in patients with schizophrenia, bipolar disorder, or major depressive disorder and healthy controls: A multiplex immunoassay study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
2
9
1
Order By: Relevance
“…In contrast to CSS, we found a significant correlation between α-MSH and cognitive function in TRS. However, similar studies are scarce, and a recent study 54 has come to the opposite conclusion from our study. We currently have an understanding of the mechanisms underlying the role of α-MSH and the DA system in feeding behavior 98 , and other investigators have explored the role of α-MSH autoantibodies (autoAbs) in impaired cognitive function 99 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to CSS, we found a significant correlation between α-MSH and cognitive function in TRS. However, similar studies are scarce, and a recent study 54 has come to the opposite conclusion from our study. We currently have an understanding of the mechanisms underlying the role of α-MSH and the DA system in feeding behavior 98 , and other investigators have explored the role of α-MSH autoantibodies (autoAbs) in impaired cognitive function 99 .…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the latest emerging study 54 , we found that the level of cognitive function in schizophrenic patients was not implicated in neuropeptide levels such as S.P and OT. In contrast, our research found that the levels of NT, BE and α-MSH were significantly correlated with cognitive function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, there was only one study comparing the differences of the plasma neuropeptides between schizophrenia, BD and MDD subjects compared with controls (56). In Hidese et al's (56) study, the authors reported there was no difference of plasma α-MSH, β-endorphin, neurotensin, oxytocin, and substance P between patient groups and controls in a larger sample size. And they did not find any significant correlation between these above-mentioned plasma neuropeptides with clinical symptom and cognitive function.…”
Section: Discussionmentioning
confidence: 91%
“…The question of the endogenous level of melanocortins in depression remains open due to the small number of studies on this topic. Some researchers indicate a reduced plasma level of α-MSH in MDD patients [ 300 ], other authors do not detect any differences in the plasma level of α-MSH between MDD patients and healthy controls [ 301 ]. There were no differences between depressed patients and healthy controls in α-MSH and ACTH levels in cerebrospinal fluid and plasma [ 302 ].…”
Section: The Effect Of Melanocortins On Depression-like and Anxious B...mentioning
confidence: 99%